Urgensi Kepemimpinan yang Unggul dalam Peningkatan Mutu Pendidikan - Muhamad Wisnu; Neng Desti Ramadhani; Istikhori Istikhori (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Improving the quality of education is one of the main priorities in developing a highly competitive human resource. In this context, excellent leadership serves as a key element that determines the direction, strategy, and success of educational transformation across all levels of education, from primary education to higher education. This article examines the urgency of visionary, inspirational, and adaptive leadership in driving the improvement of educational quality in a dynamic and complex era of change. Using a qualitative approach through literature review, policy document analysis, and observation of leadership practices, the study finds that effective educational leadership can foster a positive organizational culture, enhance motivation and participation among all stakeholders, and optimize innovation and professionalism among educators. Beyond managerial skills, excellent leadership is characterized by moral integrity, communication proficiency, collaborative abilities, and strategic decision-making skills that significantly impact learning quality. The findings indicate that educational reform cannot succeed without strong, consistent, and quality-oriented leadership. Furthermore, the development of leadership capacity within the educational ecosystem, including school principals, higher education leaders, and program administrators, should be a priority agenda in formulating policies and educational practices in Indonesia. Therefore, this article provides important implications for policymakers, educational practitioners, and researchers to design sustainable, innovative, and responsive leadership development programs. It also emphasizes the significance of leadership as a key factor in achieving high-quality, sustainable education capable of competing at the global level. The study underscores that investing in leadership development is not only a strategy to enhance educational outcomes but also a necessary step in ensuring that Indonesia’s education system can adapt to rapid changes and meet international standards.